ANTARA KONEKSI DAN KOMUNIKASI: EKSPLORASI MEDIA BARU, JARINGAN, DAN BUDAYA PHATIC DI ERA DIGITAL - Helma Winda (4, 2024)
This article explores the complex relationship between connection and communication in the context of new media, networks and phatic culture in the digital era. Through the library research method, this research explores related literature to identify and analyze trends, developments and implications of this phenomenon. The findings of this article can provide deep insight into how new media and digital networks influence the way we connect and communicate, as well as how phatic culture plays a role in these dynamics. In the shift from blogging, to social networking, to microblogging we see a shift from dialogue and communication between actors in a network, where the goal of the network was to facilitate the exchange of substantive content, to a situation where maintenance of the network itself has become the primary focus. Here communication has been subordinated to the role of simple maintenance of an ever-expanding network and the idea of ​​a connected presence. This has resulted in the emergence of what I call 'phatic media' where communication without content is preferred